2019
DOI: 10.3390/v12010010
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Wild Ungulates to the Usutu and Tick-Borne Encephalitis Viruses in France in 2009–2014: Evidence of Undetected Flavivirus Circulation a Decade Ago

Abstract: Flaviviruses have become increasingly important pathogens in Europe over the past few decades. A better understanding of the spatiotemporal distribution of flaviviruses in France is needed to better define risk areas and to gain knowledge of the dynamics of virus transmission cycles. Serum samples from 1014 wild boar and 758 roe deer from 16 departments (administrative units) in France collected from 2009 to 2014 were screened for flavivirus antibodies using a competitive ELISA (cELISA) technique. Serum sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 66 publications
1
29
0
1
Order By: Relevance
“…Comparing to the prevalence found in other European countries, the values obtained in the wild boar in the present study are higher than those reported in the Czech Republic (4.1% ) [17], similar to that reported in France in 2009-2014 (5.6% for Flavivirus and 3.4% for USUV) [26][27][28][29][30][31][32][33][34], but are lower than those reported in Spain, with a mean prevalence of 12.6% but with a significantly higher seroprevalence (27%) in wetland habitats during 2006-2010 [19], and in Serbia by [34] (17.6% WNV prevalence). In this study, only four wild boar sera showed USUV specificity.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Comparing to the prevalence found in other European countries, the values obtained in the wild boar in the present study are higher than those reported in the Czech Republic (4.1% ) [17], similar to that reported in France in 2009-2014 (5.6% for Flavivirus and 3.4% for USUV) [26][27][28][29][30][31][32][33][34], but are lower than those reported in Spain, with a mean prevalence of 12.6% but with a significantly higher seroprevalence (27%) in wetland habitats during 2006-2010 [19], and in Serbia by [34] (17.6% WNV prevalence). In this study, only four wild boar sera showed USUV specificity.…”
Section: Discussionsupporting
confidence: 78%
“…The presence of antibodies against WNV and closely related Flaviviruses, like USUV, was analyzed using a commercial competitive enzyme-linked-immunosorbent assay (ELISA ID Screen West Nile Competition Multi-Species (Innovative Diagnostics, Montpelier, France),) for detection of West Nile virus antibodies against the pr-E and pr-M envelope proteins containing an epitope common to all Flaviviruses according to the manufacturer's protocol [24][25][26]. This Elisa test has a high cross-reactivity, thus it is suitable for the detection of a wide range of flaviviruses, although it has been designed for the diagnosis of WNV infection.…”
Section: Methodsmentioning
confidence: 99%
“…These data reported, for the first time, detection of USUV in mosquitoes that concurrently accompanied the emergence of USUV in blackbirds and a human case during the period 2015–2016 [ 44 ]. A serological study conducted among wild ungulates (2009–2014) indicated the continuous circulation of USUV in southern France with seropositivity of 8.0% in wild boar and 1.0% in roe deer [ 26 ]. In addition, a serological survey conducted in 2009–2019 found low titers of USUV neutralizing antibodies in sentinel wild birds (magpie; Pica pica ) in the Camargue area [ 82 ].…”
Section: Francementioning
confidence: 99%
“…USUV RNA was also found in bats ( Pipistrellus pipistrellus ) in Germany and Belgium [ 19 , 20 ]. Moreover, USUV antibodies were sporadically detected in horses [ 21 , 22 , 23 ], dogs [ 24 ], squirrels [ 25 ], wild boar, roe deer [ 26 ] and lizards [ 27 ] ( Figure 1 ), expanding the USUV host range ( Figure 1 ), however these species are considered incidental hosts.…”
Section: Introductionmentioning
confidence: 99%
“…The recent emergence of different flaviviruses in wide regions of the world makes co-circulation of these pathogens in same geographic areas more likely (12,13,39). Furthermore, there is a range of flavivirus species sharing vectors and hosts, producing similar disease pattern in susceptible animals.…”
Section: Discussionmentioning
confidence: 99%